Constitutional rights to managing state affairs as a universal category (Journal of actual problems of jurisprudence, 2018)
This article is devoted to the problem of interaction between citizens of the Russian Federation with the state authorities and administration. The emphasis is on the interaction of the active participation of citizens in managing the affairs of the state. The constitutional establishment of the right of citizens to participate in state affairs management is focused on the electoral process and referendny, but the actual participation of citizens is beyond the scope of the constitutional institutions. Moreover, the more forms of participation of citizens will be used by them, the higher the degree of democratization in the country. However, the formalization of the participation of citizens in public management processes requires its legislative consolidation and regulation. The author focuses on the definition of the legal form of the participation of citizens in managing the affairs of the state.Key words: Legal versatility, citizens’ participation in councils, lenis state affairs, universal legal categories, government, the constitutional rights of citizens.